Structural diversity of Zeolitic imidazolate frameworks in thermoplastic Polyurethane: Integrated fire testing and hierarchical safety assessment - Yanan Hou; Mei Wan; Xiaodong Qian; Congling Shi; Ye-Tang Pan; Jiahui Shen (Polymer Testing)
Zeolitic imidazolate frameworks (ZIFs), with their unique structural attributes, have emerged as promising candidates in flame retardancy, particularly when incorporated into thermoplastic polyurethane (TPU) polymers. In this investigation, six nano-ZIFs/TPU composites were engineered through precise modulation of crystalline morphology and metal node composition, followed by systematic characterization of nano-ZIFs’ structural attributes to elucidate the influence of morphological diversity (including two types of contrast systems with the same element but different morphology and the same morphology but different elements) on flame retardancy and smoke suppression properties of TPU materials. Systematic evaluations, encompassing cone calorimetry, toxic gas analysis, and thermogravimetric profiling, demonstrated differential fire-resistant performance across ZIF types. ZIF-8 emerged as the optimal candidate: At a 2 wt% loading, TPU/ZIF-8 composites exhibited 21.91 %, 43.20 %, and 22.54 % reductions in peak heat release rate (pHRR), total smoke production (TSP), and peak CO generation rate (pCO), respectively, versus pure TPU, while retaining 14.19 % char residue at 600 °C. To systematically assess and quantify the combustion indices, an analytic hierarchy process (AHP) model containing 16 indicators was developed to evaluate the fire safety of various ZIFs. The results revealed that TPU/ZIF-8 composites exhibited the lowest fire risk index (0.8536), outperforming other polymers for fire safety. This work not only offers a novel perspective on the role of ZIFs morphology in flame retardancy but also establishes a comprehensive, efficient, and practical solution for evaluating and comparing flame retardants, thereby reducing the fire hazard of polymers.